Porous Deep Eutectic Solvents–Unfulfilled Dream or the Next Breakthrough in Scientific Innovation? - Marcin Wysokowski; Patrycja Makoś‐Chełstowska; Alina Brzęczek‐Szafran; Aleksandra Sikora; Adam Gorczyński; Teofil Jesionowski (Advanced Science)
Abstract Porous deep eutectic solvents (PDES) are capturing the imagination of scientists, promising a revolutionary leap in material science. These innovative materials, blending the versatility of deep eutectic solvents (DES) with the intricate architectures of porous structures, offer an exciting array of applications—from green chemistry and catalysis to energy storage and environmental remediation. However, the journey from laboratory curiosity to industrial application is fraught with challenges. This perspective article analyzes the realm of PDES, scrutinizing the cutting‐edge advancements and the challenges that lie ahead. By exploring their synthesis, unique properties, and diverse application potential, the critical question is asked: are PDES an unfulfilled dream or the next big breakthrough in scientific innovation? A comprehensive analysis reveals a “landscape” ripe with opportunity, suggesting that with targeted research and development, PDES can indeed become a cornerstone technology, driving progress across multiple scientific domains.